Hepatic Duct Division During Robotic Living Donor Hepatectomy: A Comparison Between the Novel Triple C (Clip–Clamp–Cut) and the Cut–Suture Techniques - Arvinder S. Soin; Kamal S. Yadav; Fysal Valappil; Nikhitha Shetty; Raghav Bansal; Suchet Chaudhary; Ankur Gupta; Amit Rastogi; Prashant Bhangui (Journal of Transplantation)
Conclusions: Our simple yet novel triple C technique enables clean, precise, bloodless HDD resulting in lower donor and potentially recipient biliary complication rates. The ease and reproducibility make it ideal for widespread adoption.